Instilling Authentic Character Education in Islamic Cultural History Subjects at the Madrasah Aliyah Level - Fani Azfar; Ahmad Barizi; Muhammad In'am Esha (al-Afkar, Journal For Islamic Studies, 2026)
This research aimed to instil authentic character education within the Islamic Cultural History course at the Islamic Senior High School (Aliyah) level. The hope is that students will become creative and independent individuals, able to contextualise each material from the Islamic Cultural History course into their own lives, according to their own needs. In its implementation, the research employed a qualitative descriptive method with a phenomenological approach. For data analysis, the Miles and Huberman theory, which consists of four stages data collection, data condensation, data display, and data verification was implemented. The results indicate that the instillation of authentic character education in the Islamic Cultural History course at the Islamic Senior High School (Madrasah Aliyah) level is found through several aspects: first, efforts to establish interaction between educators and students; second, the empowerment of learning methods aligned with efforts to develop students' authentic character; third, efforts to involve students in learning activities; and fourth, emphasizing students' contextualization of the Islamic Cultural History course material within their daily lives.